Land, Language, and Learning: Inuit Share Experiences and Expectations of Schooling - Moffat, Alesha Dawn (2018)
For decades, many Inuit have expressed the need for schooling to reflect Inuit culture, language, values, and worldview. Significant strides have been made to create a school system responsive to Inuit culture and community needs, to increase opportunities for Inuit teachers, and promote Inuit knowledge and language. Despite considerable changes since the establishment of federal day schools across the Eastern Arctic, the imposed school system retains qualities of the southern Canadian model with Qallunaat (non-Inuit) comprising the majority of teaching staff. This critical ethnography focuses on the shared experiences of schooling in Arctic Bay, Nunavut. Interviews with 24 Inuit, all of whom attended or still attend Inuujaq School, form the basis of this work. Prior teaching experience in the community, and elsewhere in Nunavut, contextualizes the research. My goal has been to come to better understandings of Inuit experiences of schooling, and the meanings Inuit attach to their experiences in the hopes that the insights offered may inform teaching practices and pedagogies and contribute to better support for Inuit students. Drawing on Indigenous thought, more specifically Inuit Qaujimajatuqangit, a holistic, diverse, and flexible theory of knowledge, grounded in Inuit culture and worldview, I explore some of the tensions and contradictions between Qallunaat teaching approaches and Inuit cultural values and educational practices through analysis of the narratives of Inuit students. I offer a historical overview of Inuit encounters with Qallunaat on Inuit lands, as well as an examination of the history of Inuit education and schooling in order to understand its influence on current schooling issues. Significantly, the interrelated themes of land, language, and learning emerged from Inuit narratives as critical pieces, central to Inuit experiences of schooling. Qallunaat teachers who choose to work in Nunavut have a responsibility to respond to the needs and desires of Inuit students. This research asks how ...